2017
DOI: 10.18632/oncotarget.22388
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-weighted MRI-derived ADC values reflect collagen I content in PDX models of uterine cervical cancer

Abstract: Apparent diffusion coefficient (ADC) values derived from diffusion-weighted magnetic resonance imaging (DW-MRI) are known to reflect the cellular environment of biological tissues. However, emerging evidence accentuates the influence of stromal elements on ADC values. The current study sought to elucidate whether a correlation exists between ADC and the fraction of collagen I-positive tissue across different tumor models of uterine cervical cancer. Early and late generation tumors of four patient-derived xenog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…In pathologic tissue alterations, for example in tumors, there is higher cellularity caused by proliferating cells, which reduces the extracellular space and consecutively reduces the proton movement overall, resulting in a lower ADC value in tumors. Moreover, it was shown that other tissue features, such as extracellular matrix proteins are also associated with ADC values (Aoyagi et al., 2012; Hauge et al., 2017). Additionally, there is an influence of perfusion to the DWI signal intensity (De Luca, Bertoldo, & Froeling, 2017; Le Bihan et al., 1988).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In pathologic tissue alterations, for example in tumors, there is higher cellularity caused by proliferating cells, which reduces the extracellular space and consecutively reduces the proton movement overall, resulting in a lower ADC value in tumors. Moreover, it was shown that other tissue features, such as extracellular matrix proteins are also associated with ADC values (Aoyagi et al., 2012; Hauge et al., 2017). Additionally, there is an influence of perfusion to the DWI signal intensity (De Luca, Bertoldo, & Froeling, 2017; Le Bihan et al., 1988).…”
Section: Discussionmentioning
confidence: 99%
“…DWI reflects random water motion in tissues and is therefore acknowledged to provide deeper insight into tissue microstructure (Surov, Meyer, & Wienke, 2017). It can be quantified by apparent diffusion coefficient (ADC), which correlates inversely with cellularity, amount of extracellular proteins and other tissue factors (Aoyagi et al., 2012; Hauge et al, 2017; Surov et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have demonstrated that ADC values are inversely correlated with IFP, using the PC method [31]. Moreover, Hauge et al demonstrated that the abundance of collagen fiber and ADC have an inverse correlation with IFP [34]. These works strongly suggest that ADC is significant for the understanding of IFP.…”
Section: Methods For Measuring Pressurementioning
confidence: 99%
“…Apparent diffusion coefficient (ADC) values derived from diffusion-weighted magnetic resonance imaging (DW-MRI) could reflect the cellular environment of biological tissues. In four cervical squamous cell carcinoma PDX models, one group observed that median tumor ADC was negatively related to the fraction of collagen I, suggesting that DW-MRI may be a non-invasive imaging approach for characterizing the stromal microenvironment of cervical cancer 29 . Consistently, four cervical cancer PDX models were used to detect the correlation between dynamic contrast-enhanced (DCE) MRI and parameters of the tumor microenvironment, and it was noticed that DCE-MRI provided valuable information on the hypoxic fraction of cervical squamous cell carcinoma 30 .…”
Section: Generation Of Pdx Modelsmentioning
confidence: 99%